Rules for Civil and Criminal Protection of Public Funds: A Comparative Study between the Saudi System and Jordanian Law (International Journal of Financial, Administrative and Economic Sciences, 2024)
Public funds are considered the cornerstone of the growth of the economy of any country in the world, as they aim to achieve the well-being of society and to build a generation that has the ability to address everything that would tamper and sabotage the people's property and public funds. Therefore, it is necessary to define the concept of audience funds by discussing the concept of public funds. Public funds and how to legally protect public funds from any attack that may occur on them.Based on the foregoing, the study was divided into two sections. The first section dealt with the concept of public funds. The topic was divided into two requirements. The first dealt with the definition of public funds. In the second requirement, the researcher dealt with methods of acquiring public money. The second topic included legal protection for public funds by dividing the topic into two requirements. In the first requirement, the study presented the civil protection of public funds, and in the second requirement, the researcher dealt with the penal protection of public funds in the Saudi and Jordanian systems.
Keywords: Public Money; Hand Mode; Methods of Acquiring Public Money; Legal Protection of Public Money; Civil Protection for Public Money; Penal Protection of Public Money; The Crime of Embezzlement